The Ancient World 1200 B.C. to A.D. 500. Translated from the Italian by Guy E. F. Chilver and Sylvia Chilver. Foreword by René Mehau. Preface by Paulo E. de Berrêdo Carneiro. Part I - Pareti, Luigi (1965)
assisted by Paolo Brezzi and Luciano Petech; vol. I = 26:с:728; Part I: From about 1200 B.C. to about 500 B.C. (I. The Chief Historical Events; II. The Evolution of Languages and Writing Systems; III. Technology, Trade, Science; IV. Political Organization and Social Life; V. Religion and the Beginnings of Philosophy; VI. Literature and Art); Published for the International Commission for a History of the Scientific and Cultural Development of Mankind by George Allen and Unwin Ltd.